Pelayanan Polisi Pamong Praja dalam Ketertiban dan Keamanan Pedagang Kaki Lima di Pasar Pangkajene - Muhammad Ali (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
The purpose of this research was to investigate the services performance of Municipal Police Force in Sidenreng Rappang Regency, along with all factors that influenced it. This research’s type was quantitative research with a descriptive approach to describe the Municipal Police Force performance. Data collection methods used were direct observation, interviews, questionnaires, and library research to selected respondents. The population took 217 people with a sample of 43 people. While the data processing techniques used were frequency tables distribution. The results showed that the Municipal Police Force service in the field of law and order against street vendors in Pangkajene public market was considered good at 44,19% and scored 3,14 in good category, while the influencing factors were considered excellent at 77,33% and scored 4,39 in very good category.